(untitled) (Jurnal Manajemen dan Organisasi, 2016)
The objectives of this study are (1) to find the effectiveness of social media used by Wall’s Magnum ice cream based on the characteristics of the expenditure and (2) to analyze the factors that influence consumer purchasing decisions of Wall’s Magnum ice cream based on characteristics of the expenditure. The research framework is using the Consumer Decision Model which analyze by regression analysis and consumer purchasing decisions model which analyze by descriptive analysis. The correlations between both models were analyzed by Canonical Correlation using of MINITAB 14, SPSS 16.00, Ms Excel and STATISTICA 8. The path analysis by CDM model for respondent with ≤ Rp 800,000 expenditure and for respondent with > Rp 800.000 were showing effectiveness of information about Wall’s Magnum sent through social media. However, the path analysis showed that CDM model for respondent with ≤ Rp 800,000 expenditure is more effective rather than the CDM model and for respondent with > Rp 800.000. The results of canonical correlation analysis showed the most influencing factors on purchase decisions for respondent with the expense ≤ Rp 800,000 are brand and place of purchase, mean while the most influencing factors for respondent with the expenditure> Rp 800,000 are previous experience and packaging.